2013
DOI: 10.1186/1471-2458-13-1026
|View full text |Cite
|
Sign up to set email alerts
|

Coverage and parental perceptions of influenza vaccination among parents of children aged 6 to 23 months in Hong Kong

Abstract: BackgroundThe impact of influenza on young children can be severe and even fatal. Influenza vaccination (IV) has been shown to be effective in reducing complications of influenza among children. This study investigated the prevalence and factors of IV among children aged 6-23 months in Hong Kong.MethodsA sample of 401 Chinese parents of children aged 6-23 months were interviewed at local Maternal and Child Health Centers. Socio-demographic information, variables related to Health Belief Model, including percep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
53
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(61 citation statements)
references
References 53 publications
(47 reference statements)
6
53
1
1
Order By: Relevance
“…China and Thailand have recently launched public health initiatives to encourage early childhood influenza vaccination. However, even in these countries, recent estimates of childhood vaccine coverage are relatively low (and quite variable), ranging from 1% (60) to 30% (61) in Thailand, and from 26% (62) in China to <9% (63) in Hong Kong. For all other countries in our study, conservative estimates based on the number of vaccine doses purchased (50) show that even in the upper-bound limit that all vaccine doses were administered, and were distributed exclusively among children ages 0-9 years, childhood coverage would remain well below 5% in these countries (details below).…”
Section: Reconstructing Immune Imprinting Patterns With Vaccinationmentioning
confidence: 99%
“…China and Thailand have recently launched public health initiatives to encourage early childhood influenza vaccination. However, even in these countries, recent estimates of childhood vaccine coverage are relatively low (and quite variable), ranging from 1% (60) to 30% (61) in Thailand, and from 26% (62) in China to <9% (63) in Hong Kong. For all other countries in our study, conservative estimates based on the number of vaccine doses purchased (50) show that even in the upper-bound limit that all vaccine doses were administered, and were distributed exclusively among children ages 0-9 years, childhood coverage would remain well below 5% in these countries (details below).…”
Section: Reconstructing Immune Imprinting Patterns With Vaccinationmentioning
confidence: 99%
“…For 2007 and 2009, the influenza A H1N1 strains were not matched while influenza B strains were not matched in 2008. However, data suggested the uptake rate among infants 6-23 months was low at 8.5% during the 2005/6 flu season [8], but the introduction of governmental subsidies to influenza vaccination for aged 6-59 months since 2008 may have improved vaccine uptake. Pregnant women are a high risk group that can benefit from seasonal influenza vaccination and recent studies have suggested that their infants will also enjoy some degree of protection [9][10][11][12][13][14][15][16].…”
Section: Discussionmentioning
confidence: 99%
“…A variety of theoretical frameworks were used to inform the design of the questionnaires used in the studies. The most common was the Health Belief Model (HBM), which was explicitly stated as having been used to inform the questions in 22 (19.0%) studies (26,28,(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49), followed by the Theory of Planned Behaviour, which was used in 5 (4.3%) studies (50)(51)(52)(53)(54)(55). Other studies that were adapted from existing questionnaires may have implicitly been based on these or other theoretical frameworks as a consequence of having adapted from other questionnaires but did not explicitly claim the theoretical framework as a basis for their questions.…”
Section: Use Of Questionnaires and Survey Instrumentsmentioning
confidence: 99%
“…All studies identified an association between attitudes and beliefs with vaccination status, with concern about safety and efficacy the most commonly reported associations with lower vaccine uptake. In 26 of the 57 studies, an association between vaccination status and beliefs about the safety of vaccines were identified(29,39,40,48,49,55, and these studies were most commonly conducted in the United States (n=9) and China (n=4). Among the 26 studies that found an association between vaccination status and beliefs about the safety of vaccines, participants were asked about all childhood vaccines in 10 studies(55, 63,(67)(68)(69)(70)(71)(72)(74)(75)(76), and about influenza vaccines in 12(39, 40, 49, 64-66, 73, 77, 79-81, 83).…”
mentioning
confidence: 99%